How Transnational is "Transnational"?: foreign Fighter Recruitment and Transnational Operations among Affiliates of al-Qaeda and the Islamic State - Krause, Dino (Perspectives on terrorism, 2022)
To this date, there are no instances of peace agreements signed by armed groups affiliated with al-Qaeda or the Islamic State (IS). Previous research has highlighted their transnational demands and their integration into a transnational organization as major obstacles. Yet, these groups are also deeply embedded within local conflict configurations. This article posits that to explore prospects for future negotiations with these groups, one must obtain a better understanding of how they function on the ground. A descriptive empirical analysis is provided of two dimensions of ‘transnationalization’ that should both have an impact on jihadist affiliate groups’ willingness to enter negotiations: transnational operations and transnational recruitment. The analysis of a sample of twenty jihadist affiliate groups in the period 2018-2020 reveals substantial variation regarding both variables. The results should have relevance for both researchers and policymakers seeking to identify nonviolent containment strategies in armed conflicts with rebel groups affiliated with al-Qaeda and IS.